Case-based methods and agent-based modelling: bridging the divide to leverage their combined strengths. Issue 4 (4th July 2019) - Castellani, Brian; Barbrook-Johnson, Peter; Schimpf, Corey
ABSTRACT: Two leading camps for studying social complexity are case-based methods (CBM) and agent-based modelling (ABM). Despite the potential epistemological links between 'cases' and 'agents, ' neither camp has leveraged their combined strengths. A bridge can be built, however, by drawing on Abbott's insight that 'agents are cases doing things', Byrne's suggestion that 'cases are complex systems with agency', and by viewing CBM and ABM within the broader trend towards computational modelling of cases. To demonstrate the utility of this bridge, we describe how CBM can utilise ABM to identify case-based trends; explore the interactions and collective behaviour of cases; and study different scenarios. We also describe how ABM can utilise CBM to identify agent types; construct agent behaviour rules; and link these to outcomes to calibrate and validate model results. To further demonstrate the bridge, we review a public health study that made initial steps in combining CBM and ABM.